Using the International Model of the Qatar University Arabic Debating Championship (IUADC) to Practice Critical Thinking at the Namlah Student Activity Unit, Universitas Muhammadiyah Surakarta - Bahtiar, Luth Hafizh; Azani, Mohammad Zakki; Maksum, Muhammad Nur Rochim (Maharaat: Jurnal Pendidikan Bahasa Arab, 2023)
The research background indicates a decline in the critical thinking skills of the Indonesian population, as evidenced by PISA data. Indonesians remain susceptible to misinformation due to insufficient literacy and critical thinking abilities. The researcher aims to disseminate information regarding the Qatar debate competition model, which may be unfamiliar to our academics. Indonesia secured first place in the international Arabic language debate, an achievement that is not widely recognized. The Namlah student activity unit is affiliated with the University of Muhammadiyah Surakarta and focuses on Arabic debate. Namlah has participated in multiple debate competitions, including the Arabic language festival at UNS, the UADC-UII in Yogyakarta, and the MTQMN in Aceh. The researcher aims to examine the potential of the Qatar Debate Model System, which utilizes the Asian parliamentary framework, in enhancing students' critical thinking abilities. This field research employs qualitative methods, utilizing data collection techniques such as observation, documentation, and interviews, which are subsequently validated through a credibility assessment. Analysis of data involving reduction, presentation, and conclusion. The study's results indicate that the IAUDC model enhances students' critical thinking abilities, with 12 indicators derived from Ennis' theory effectively implemented through this model.